Monitoring the Socio-Economic Impacts of COVID-19 on Djiboutian and Refugee Households in Djibouti : Results from the Third Wave of Survey - Malaeb, Bilal; Duplantier, Anne; Gansey, Romeo Jacky; Konate, Sekou Tidani; Abdoulkader, Omar; Tanner, Jeff; Mugera, Harriet (World Bank, Washington, DC, 2021)
The third round of data collection on monitoring of socio-economic impacts of the COVID-19 (coronavirus) pandemic in Djibouti followed urban national households based on two previous waves of data collection as well as a replacement sub-sample. This round also includes a refugee sub-sample, covering urban refugees and those based in refugee villages. Economic recovery in Djibouti continues to follow a positive trend. Breadwinners from Djiboutian households continue to come back to work. Only 4 percent of those working before the pandemic were not working at the time of the survey. Even when counting those who were not working before the pandemic, 83 percent of all national households' breadwinners are now working – continuing strong trends from waves 1 and 2. Nationals with waged work grew from 22 to 76 percent in that time, and only 9 percent of those currently working report working less than usual. Djiboutian workers are also working more – but for less pay. Only one in five Djiboutian breadwinners are working less than they were before the pandemic or not at all. However, half of those who worked less than usual received no pay in wave 3 – 53 percent up from 35 percent in wave 2, and fewer received partial payment compared to the previous waves. Poor households were more likely to have received no pay for work performed. Refugees based in refugee villages face worse employment conditions than those living in urban areas or urban nationals. They were less likely to be employed prior to COVID-19, more likely to lose their job during pandemic, and do not exhibit similar signs of recovery. Around 68 percent of urban refugee breadwinners are currently working and 7 percent who worked before the pandemic are currently not working. In comparison, less than half (49 percent) of refugee breadwinners based in refugee villages are currently working, and 16 percent are no longer working relative to pre-COVID-19. A quarter of urban refugees and around 35 percent of refugees in refugee villages worked neither now nor before the pandemic, and nearly a third (29 percent) of the latter who are working report working less than usual. In addition, refugee breadwinners’ concentration in the informal sector (87 percent) highlights the precarity of their livelihood.